Rapid label-free visual detection of KRAS mutations using peptide nucleic acid and unmodified gold nanoparticles. Issue 77 (16th October 2017) - Zhao, Xihong; Lin, Chii-Wann
Abstract : Colorectal cancer (CRC) is among the most commonly diagnosed cancers worldwide. Abstract : Colorectal cancer (CRC) is among the most commonly diagnosed cancers worldwide. Point mutations on the Kisten rat sarcoma viral oncogene homologue (KRAS) have been identified as a crucial diagnostic and prognostic biomarker for response to cancer therapy targeting the epidermal growth factor receptor. A rapid label-free colorimetric assay for detection of point mutations in codon 12 and 13 of the KRAS gene using peptide nucleic acid (PNA) and unmodified gold nanoparticles (AuNPs) was presented in this study. Charge neutral PNA induces the AuNPs aggregation in the absence of complementary DNA; when the complementary DNA is present, PNA–DNA hybridization retains the dispersion of AuNPs as the negative charges of the DNA strand adsorbed on the AuNPs surface ensure sufficient charge repulsion. Based on this principle, the developed assay was able to detect the specific sequence in the presence of at least 20 times the amount of interference oligonucleotides, and the limit of detection was low as DNA/PNA ratio of 0.02. The PNA induced colorimetric changes in the presence of the complementary DNA at different ratios of DNA/PNA yielded a standard curve with a linear coefficient of R 2 = 0.9371. Furthermore, this assay was validated in order that it could be used to detect the seven known mutant alleles in codon 12 and 13 of the KRAS gene by the naked eye with higher concentration of PNA. This simple colorimetric assay is rapid, sensitive and easily performed at room temperature without additional stringent conditions, which promises the method great potential utility for clinical sample screening and point-of-care testing.